Functional trait trade‐off and species abundance: insights from a multi‐decadal study. (27th January 2019) - Ge, Xing‐Yue M.; Scholl, Joshua P.; Basinger, Ursula; Huxman, Travis E.; Venable, D. Lawrence
Abstract: Phylogenetically informed trait comparisons across entire communities show promise in advancing community ecology. We use this approach to better understand the composition of a community of winter annual plants with multiple decades of monitoring and detailed morphological, phenological and physiological measurements. Previous research on this system revealed a physiological trade‐off among dominant species that accurately predicts population and community dynamics. Here we expanded our investigation to 51 species, representing 96% of individual plants recorded over 30 years, and analysed trait relationships in the context of species abundance and phylogenetic relationships. We found that the functional‐trait trade‐off scales to the entire community, albeit with diminished strength. It is strongest for dominant species and weakens as progressively rarer species are included. The trade‐off has been consistently expressed over three decades of environmental change despite some turnover in the identity of dominant species.